Digitalisasi Administrasi Publik Meningkatkan Efisiensi Sistem Pelayanan Publik Dalam Good Governance dan Kinerja Pegawai di Kecamatan Cidadap - Maulidini, Jamillatul; Nabila, Ellisa Amel; Bilfaqih, Nabila; Azhar, Tami Nafilah; Ariesmansyah, Andre (Innovative: Journal Of Social Science Research, 2025)
This research aims to analyze the efficiency of the public service system in good governance and employee performance organized by the Cidadap District Office, Bandung City in improving service quality in accordance with the expectations of the community as service users. The implementation of good governance can be seen from the application of the principles of participation, rule of law, transparency, responsiveness, consensus orientation, fairness, effectiveness and efficiency, accountability and strategic vision. Employee performance can be seen from productivity, service quality, responsiveness, responsibility and accountability for public sector performance. This research uses a literature study research method. The results of the research show that the Cidadap District Office, Bandung City has implemented good governance well, so that the services provided to the community can be carried out better. The obstacles experienced include the fact that not all people understand the applicable Standard Operating Procedures, so it is necessary to carry out communication and outreach through various outreach to the community so that service requests and service delivery can be carried out better. Through analysis, service quality is generally good, including employees who have a neat appearance, adequate infrastructure and friendly employee attitudes.